Pelayanan Berkualitas, Santri Puas: Mengungkap Peran Koperasi Pesantren Al-Kautsar Dendang - Rudianto, Rudianto; Pitri, Alisyah; Edi Saputra, Ahmad (Innovative: Journal Of Social Science Research, 2025)
The advancement of time demands educational institutions, including Islamic boarding schools (pesantren), to not only focus on religious education but also equip students (santri) with economic skills to enhance their independence. This study aims to analyze the effectiveness of economic empowerment through the Al-Kautsar Dendang Cooperative and identify supporting and inhibiting factors affecting service quality and student satisfaction. Using a descriptive qualitative approach through observation, interviews, and literature studies, the research found that the cooperative plays a strategic role in meeting students' needs, providing academic supplies, and teaching Sharia-based economic principles. The success of the cooperative is supported by good management and active involvement from the pesantren; however, it still faces challenges such as limited resources and low financial literacy among students. Therefore, optimizing management strategies and entrepreneurship education is essential to enable pesantren cooperatives to contribute more significantly to improving students' welfare and fostering independent, competitive individuals in the modern era